2022
DOI: 10.1093/cdn/nzac007
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Malnutrition and Physical Performance in Older Adults: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: In recent years the focus of healthcare and nutritional science in older adults has shifted from mortality towards physical performance and quality of life. The aim of this review was to summarize observational studies on physical performance in malnourished (MN) or at-risk of malnutrition (RMN) older adults compared to well-nourished (WN) older adults. Eligible studies had to report on nutritional status and objectively measured physical performance in older adults (≥60 years). MN or RMN groups had to be comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Gait speed as a categorical variable has also been associated with RM, as this condition was less likely to occur in community-dwelling older adult subjects with healthy values (≥0.8 m/s) [24]. Kramer et al (2022) [44] published similar findings. Results of this meta-analysis considering only cross-sectional studies, including the study published by Chatindiara et al (2018) [24], showed that well-nourished groups walked significantly faster than those with RM.…”
Section: Previous Studies Related To the Causality Of Risk Of Malnutr...mentioning
confidence: 89%
See 2 more Smart Citations
“…Gait speed as a categorical variable has also been associated with RM, as this condition was less likely to occur in community-dwelling older adult subjects with healthy values (≥0.8 m/s) [24]. Kramer et al (2022) [44] published similar findings. Results of this meta-analysis considering only cross-sectional studies, including the study published by Chatindiara et al (2018) [24], showed that well-nourished groups walked significantly faster than those with RM.…”
Section: Previous Studies Related To the Causality Of Risk Of Malnutr...mentioning
confidence: 89%
“…That published work reported that high age, low self-perceptions of health, and depressive symptoms were factors strongly associated with RM at follow-up [16]. The results of several published cross-sectional studies [3,4,[9][10][11][12]15,23,24] and a recently published systematic review and meta-analysis of cross-sectional studies [44] on the association between risk factors and RM in older populations led us to hypothesize that excess fat mass, low TLT, low gait speed, and low handgrip strength, separately, could be associated with RM at follow-up in community-dwelling older people. Results of the present cohort study also found that RM is less likely to occur in subjects with excess fat mass (measured by DXA and diagnosed by the FMI classification) assessed as the categorical variable.…”
Section: Previous Studies Related To the Causality Of Risk Of Malnutr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of malnutrition on body composition is so significant that the reduction of muscle mass is one of the diagnostic criteria for malnutrition in the latest consensus from the global clinical nutrition community (GLIM) [ 71 ]. Malnutrition, sarcopenia, and physical performance are interrelated and share numerous risk factors [ 72 , 73 ]. The loss of muscle, reduced muscle strength, and physical performance are the key changes that lead to sarcopenia, and sarcopenia is one of the most important risk factors for frailty [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is a key factor for sarcopenia (16,17) . Malnutrition, including undernutrition and overnutrition, and low physical activity may be associated with sarcopenia and sarcopenic obesity (18,19) . Examining the nutritional status of MS patients in clinical or community settings is a pressing issue for dietitians.…”
mentioning
confidence: 99%